Mengarusutamakan Pemerintahan Cergas melalui Aplikasi SiBakul Jogja selama Masa Pandemi COVID-19 - Syafiqurrohman, Ahmad; Atmojo, Muhammad Eko (Nakhoda: Jurnal Ilmu Pemerintahan, 2023)
The COVID-19 pandemic has affected various sectors, one of which is the economic sector, which includes MSMEs. Government innovation is needed to bridge MSMEs so they can survive amid the COVID-19 Pandemic crisis, one of which is through the SiBakul Jogja platform. The purpose of this study is to examine the implementation of the SiBakul Jogja platform through an agile governance perspective as an innovation from the DIY Provincial Government. The research method used is a qualitative case study approach. Data collection techniques with triangulation, namely interviews and documentation. The results of the study show that SiBakul Jogja has a system that reflects the application of Agile Governance as one of the DIY UKM Diskop innovations. Some of them are Business Driven which were developed concurrently with system updates related to the Systematic and adaptive approach. However, SiBakul Jogja still has weaknesses in terms of responsiveness from public complaints, especially in the SiBakul Jogja system which is related to Human Focused. Through its various features to facilitate KUMKM data integration, in fact not all features can function optimally. In fact, one of its features, namely MarketHub and the Kotagede YIA Market Gallery, has high traffic because it is close to people's needs. The conclusion of this study illustrates that SiBakul Jogja as a Government innovation has not been fully capable of implementing agile governance.